Comprehensive and quantitative study on the thermal oxidative stabilization reactions in poly(acrylonitrile‐co‐itaconic acid) copolymer. Issue 9 (6th November 2017) - Fu, Zhongyu; Liu, Baijun; Li, Bing; Liu, Yuyao; Zhang, Huixuan
ABSTRACT: Thermal oxidative stabilization (TOS) reactions, mainly cyclization, oxygen uptake, dehydrogenation, crosslinking, and disproportionation termination of cyclization in poly(acrylonitrile‐ co ‐itaconic acid) (PAI), are tracked quantitatively by the combination of second‐derivative and cure‐fitting operations in the Fourier transform infrared spectroscopy spectra (FTIR) range of 1800–1000 cm −1 and 2300–2100 cm −1 . Except the cyclization and disproportionation of cyclization are chemical‐reaction‐controlled process, the other three reactions are both diffusion‐controlled and chemical‐reaction‐controlled processes. The formation of free and conjugated carbonyl group need the optimal cyclization rate, adequate unreacted linear PAI chains, and appropriate oxidation ability coordinated. The higher temperature, the faster rate and the higher extent of the cyclization and the crosslinking reactions as well as the faster disproportionation termination of cyclization. The length of the formed cyclic structures became shorter as the evolution of TOS process, especially for 265 °C. The crosslinking, oxygen uptake, dehydrogenation, and termination of cyclization reactions become dominant with the proceeding of TOS process, especially as the cyclization extent above 0.8 and at high temperature such as 265 °C. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45934. Abstract :